Nigerian Federalism: The Quest for Restructuring - AYOTUNDE DAVID ODEWALE; BANJI MARCELLINUS ADEPOJU; KEHINDE REBECCA KAREEM (Jurnal Studi Pemerintahan, 2023)
The quest for restructuring Nigeria’s federal system has been a frequent tune from most of her citizens. This challenge has created a wide gap in the federation which threatens the sovereignty of the nation. These agitations for secession/disintegration, and restructuring from different strata of the nation have constituted a major threat to Nigerian sovereignty. Hence, the study looks at the make or mar locus confronting Nigeria federal system. Primary and secondary data were used for this study; the primary data were gathered through the use of a questionnaire, while content analysis was used for secondary data. The study revealed some issues involved in the agitation for restructuring which includes among others, the secession of some federating units, the creation of additional states, corruption, leadership crises, and the poor state of the country’s economy. Hence, the study recommends that there is an urgent need to restructure Nigeria’s federalism structure, especially the constitutional review that would involve all ethno- regional entities of the federation to engender equity and equality. The study concludes that until the political leaders reform the institutions and structures of the federal system, Nigeria’s nation may not attain its potential.